The Place of Dipeptidyl Peptidase-4 Inhibitors in Type 2 Diabetes Therapeutics: A “Me Too” or “the Special One” Antidiabetic Class? - Ricardo Godinho; Cristina Mega; Edite Teixeira-de-Lemos; Eugénia Carvalho; Frederico Teixeira; Rosa Fernandes; Flávio Reis (Journal of Diabetes Research)
Incretin-based therapies, the most recent therapeutic options for type 2 diabetes mellitus (T2DM) management, can modify various elements of the disease, including hypersecretion of glucagon, abnormal gastric emptying, postprandial hyperglycaemia, and, possibly, pancreatic β cell dysfunction. Dipeptidyl peptidase-4 (DPP-4) inhibitors (gliptins) increase glucagon-like peptide-1 (GLP-1) availability and correct the “incretin defect” seen in T2DM patients. Clinical studies have shown good glycaemic control with minimal risk of hypoglycaemia or any other adverse effects, despite the reports of pancreatitis, whose association remains to be proved. Recent studies have been focusing on the putative ability of DPP-4 inhibitors to preserve pancreas function, in particular due to the inhibition of apoptotic pathways and stimulation of β cell proliferation. In addition, other cytoprotective effects on other organs/tissues that are involved in serious T2DM complications, including the heart, kidney, and retina, have been increasingly reported. This review outlines the therapeutic potential of DPP-4 inhibitors for the treatment of T2DM, focusing on their main features, clinical applications, and risks, and discusses the major challenges for the future, in particular the possibility of becoming the preferred therapy for T2DM due to their ability to modify the natural history of the disease and ameliorate nephropathy, retinopathy, and cardiovascular complications.